1998
DOI: 10.1083/jcb.143.2.533
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Mammary Gland Development In Vitro: Requirement of c-met and c-erbB2 Signaling for Branching and Alveolar Morphogenesis

Abstract: We have established a cell culture system that reproduces morphogenic processes in the developing mammary gland. EpH4 mouse mammary epithelial cells cultured in matrigel form branched tubules in the presence of hepatocyte growth factor/scatter factor (HGF/SF), the ligand of the c-met tyrosine kinase receptor. In contrast, alveolar structures are formed in the presence of neuregulin, a ligand of c-erbB tyrosine kinase receptors. These distinct morphogenic responses can also be observed with selected human mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
115
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 105 publications
(140 reference statements)
8
115
1
Order By: Relevance
“…Consistent with these results, we have previously reported that NRG1 implanted within mammary glands of virgin female mice, induced the formation of alveoli with an accumulation of the lactation product b-casein (Jones et al, 1996). In addition, ectopic expression and activation of ErbB2 signaling, in the absence of activated coreceptors, induced alveolar-like structures in cultured mammary epithelial cells identical to those induced by NRG1 treatment (Niemann et al, 1998). Collectively, these results suggest that NRG1 plays a role in lobuloalveolar maturation and lactation by activating ErbB2 signaling at parturition.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Consistent with these results, we have previously reported that NRG1 implanted within mammary glands of virgin female mice, induced the formation of alveoli with an accumulation of the lactation product b-casein (Jones et al, 1996). In addition, ectopic expression and activation of ErbB2 signaling, in the absence of activated coreceptors, induced alveolar-like structures in cultured mammary epithelial cells identical to those induced by NRG1 treatment (Niemann et al, 1998). Collectively, these results suggest that NRG1 plays a role in lobuloalveolar maturation and lactation by activating ErbB2 signaling at parturition.…”
Section: Discussionmentioning
confidence: 60%
“…In the AU565 human breast cancer cell line, NRG1 induces a di erentiation phenotype Peles et al, 1992) which requires ErbB2 expression (Yoo and Hamburger, 1998). Moreover, activated ErbB2 is capable of forming alveolar-like structures in mammary epithelial cells identical to those observed following NRG1 treatment (Niemann et al, 1998). In vivo, lobuloalveoli induced by mammary implants containing NRG1, but not TGFa, produce secretory products including the milk-protein b-casein (Jones et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Previously reported in vitro and in vivo experimental systems corroborate a role for HRGa signaling in b-casein gene expression. HRG1 stimulated expression of b-casein in mammary gland organ cultures (Yang et al, 1995) and collagen cultures of EpH4 mammary epithelial cells (Niemann et al, 1998). Furthermore, Elvax pellets containing HRGa induced b-casein expression and secretion when implanted within the mammary glands of nulliparous mice (Jones et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HRG1 induces functional differentiation of the human breast cancer cell lines AU565 (Chen et al, 1996;Peles et al, 1992), SkBr-3 (Le et al, 2000), and MCF-7 (Chen et al, 1996). Similarly, matri-gel collagen matrix cultures of the EpH4 mammary epithelial cell line and human breast tumor explants undergo functional differentiation, forming alveoli-like structures and expressing the milk protein b-casein, when treated with HRG1 (Niemann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The related biologic activities of HRG and HER-2 are supported by experiments in which these genes were either knocked out and/or mutated in mice, resulting in similar embryonic heart malformation and defects in the development of the neural system, causing embryonic death at day 11 (Meyer and Birchmeier, 1995;Lee et al, 1995). In addition, studies aimed at testing the e ect of HRG on mammary gland development in vivo, mouse mammary epithelial cells cultured in matrigel, as well as mammary carcinoma tissue in explant culture, demonstrate response to addition of HRG by forming alveolar structures and this morphogenic e ect is dependent on HER-2 activation of the MAPK kinase signaling pathway (Niemann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%